Quad separation algorithm for bounding-volume hierarchies construction in virtual environment application - Sulaiman, Hamzah Asyrani; Bade, Abdullah; Abdullah, Mohd Harun; Othman, Mohd Azlishah; Ismail, Mohd Muzafar; Misran, Mohamad Harris; Meor Said, Maizatul Alice; Ramlee, Ridza Azri (2013)
In order to perform fast collision detection technique in Virtual Environment Application, researchers need to maintain the behaviour of the object itself before the objects come into contact. By enhancing the speed of intersection using Bounding-Volume Hierarchies technique, it helps to reduce the complexity and speed up the intersection process. Thus, in this paper we presented our novel algorithm for constructing Bounding-Volume Hierarchies using Quad Splitting method. Together with the Quad Splitting method is the implementation of Spatial Object Median Splitting technique (SOMS) in order to create a well-balanced tree for the object. We believed the key of performing fast intersection between two or more objects in Virtual Environment Application required a well-balanced and proper tree technique for Bounding-Volume hierarchies.